IMPLEMENTATION OF THE SQ3R STRATEGY TO IMPROVE STUDENTS' READING COMPREHENSION ABILITY (International Conference on Social and Islamic Studies, 2022)
Implementation of SQ3R Strategy to Improve Students' Reading Comprehension Ability. This study uses a classroom action research design with the aim of improving students' reading comprehension skills by applying the Survey, Question, Reading, Recite, Review (SQ3R) strategy. The subjects of this study were students of class V MIS Muhammadiyah Lautang Salo. The improvement targets include the implementation of the learning process and results. This research design uses a cycle research design, consisting of planning, action, observation, and reflection stages. Data collection uses two techniques, namely test and non-test. Tests in the form of essays are carried out before the implementation of the action and at the end of each cycle. Non-test in the form of: (1) observations, (2) interviews, (3) field notes, and (4) documentation. The test data were processed and presented in a tabulated matrix, then analyzed descriptively qualitatively. Meanwhile, the process data were analyzed in the following stages: (1) analyzing the data; (2) reduce data; (3) Presentation of data; (4) draw conclusions. The results of data analysis showed that the students' pre-action ability was only 50% (out of 12 students who attended), the first cycle was 54% or 8 students (out of 15 students), and the second cycle was 12 students or 80%. Based on the results of the study, it can be concluded that the application of the SQ3R method can improve students' reading comprehension skills. This can be seen from the increase in the number of students who achieved learning mastery scores, namely in the first cycle, eight students were obtained to twelve students in the second cycle. Based on the results of the research, it is suggested to use the SQ3R strategy as one of the teacher's choices in teaching reading in elementary schools.